Exploring specific learning difficulties in primary schools: An empirical research - Sukadari; Jandra M.; Sutarto; Hehsan A.; Junaidi J.; Huda M. (Mattingley Publishing, 2023)
Identification (control systems); Students; Surveys; Academic assessment; Learning difficulties; Primary schools; Specific learning; Student learning; Learning systems